Tathwiir Wasiilah Ta’liim Al-Mufradaat Bi Istikhdaam Lu’bah Bithaaqah Karuta Li Al-Mustawa Al-Tsaanawiyah Li As-Shaf Ats-Tsaamin - Elya Ditarahmi (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
Media is a tool to provide incentives for students so that the learning process occurs. Karuta card game is a picture card game from Japan. This research is a development research with 4D model which consists of four steps, namely: define, design, develop, and disseminate. However, the researcher limits the development procedure only to limited trials for teachers and students. The development procedure in this research is: the define stage or called needs analysis stage. This stage consists of five steps, namely front and analysis, learner analysis, task analysis, concept analysis, and specifying instructional objectives. The results that researchers get from this stage are this media needs to be develop. Then the design stage: looking for vocabulary, design karuta card, design control book, score book, and game rule book, print karuta card, and make a box of karuta cards. Then, the last stage is the develop stage, namely: expert validation test, the result is “Valid” in terms of media and “Very Valid” in terms of material. Then limited trial for teachers and students, the result is “Very Practical” which means that karuta card game can be used in vocabulary learning for eight grade in State High Schools.